A legal history for Australia - McKibbin, Sarah; Connors, Libby, 1960-; Harmes, Marcus K. (London, England : Zed Books, 2021)
"This is a contemporary legal history book for Australian law students, written in an engaging style and rich with learning features and illustrations. The writers are a unique combination of talents, bringing together their fields of research and teaching in Australian history, British constitutional history and modern Australian law. The first part provides the social and political contexts for legal history in medieval and early modern England and America, explaining the English law which came to Australia in 1788. This includes: The origins of the common law The growth of the legal profession The making of the Magna Carta The English Civil Wars The Bill of Rights The American War of Independence. The second part examines the development of the law in Australia to the present day, including: The English criminal justice system and convict transportation The role of the Privy Council in 19th century Indigenous Australia in the colonial period The federation movement Constitutional Independence The 1967 Australian referendum and the land rights movement. The comprehensive coverage of several centuries is balanced by a dynamic writing style and tools to guide the student through each chapter including learning outcomes, chapter outlines and discussion points. The historical analysis is brought to life by the use of primary documentary evidence such as charters, statutes, medieval source books and Coke's reports, and a series of historical cameos - focused studies of notable people and issues from King Edward I and Edward Coke to Henry Parkes and Eddie Mabo - and constitutional detours addressing topics such as the separation of powers, judicial review and federalism. A Legal History for Australia is an engaging textbook, cogently written and imaginatively resourced"--
The origins of the common law -- The intellectual life of the law and lawyers from the middle ages to Edward Coke -- The English revolutions : parliament, the king, and the law courts -- Responsible government, law, and justice in eighteenth-century England -- The American constitutional settlement -- Reform of British Parliament, society, and courts in nineteenth-century England -- The reception of English law in Australia -- Self-government and law in colonial Australia -- Indigenous Australia and the law in the colonial period -- Federation -- Australian constitutional independence and legal developments of the twentieth century -- The painful legacy of colonialism : aboriginal and Torres Strait islander people and the law in modern Australia.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law -- Australia -- History; Legal history; Electronic books